(untitled) (Journal of Economic Additions, 2019)
The objective of our study is to evaluate the effectiveness of the tax audit and the tax control in the Algerian environment, the tax audit is considered as a very important tool in the improvement of the tax management of the economic companies thus to prevent tax risks to which companies can compete in order to reduce the tax costs of companies, however, tax control is one of the most important means available to the states to ensure the recovery of taxpayer’s taxes to the public treasury as well as to fight tax evasion. Through the study carried out it proved the effectiveness of the tax audit for the economic companies by the reduction of the tax costs and the improvement of the fiscal management and that from the point of view of the economic companies in Ouargla, also reached the objectives set to prove the effectiveness of tax control in the Algerian environment by promoting tax recovery and the fight against tax fraud as well as to bring a positive effect on the tax management of economic companies and that from the point of view of the tax administration in Ouargla Key words: tax audit; tax control; tax management; tax costs; tax recovery. Jel Classification codes: M41.